Performance Diagnosis of Horses - Eric, Barrey (Biology - Book Archive pre-2000, 1997)
The objective of the book is to inform all persons involved in the equine breeding and sports industry about the practical use of measurements of biochemical and physiological variables for the determination of athletic potential of horses. Great care was taken to differentiate between the effects of exercise and the effects of training. "...There is some very good material to be found here..." (Journal of equine veterinary science)